The E3 ubiquitin ligase HECW1 targets thyroid transcription factor 1 (TTF1/NKX2.1) for its degradation in the ubiquitin-proteasome system - Liu, Jia (Cell Signal, 2019)
Thyroid transcription factor 1 (TTF1/NKX2.1), is a nuclear protein member of the NKX2 family of homeodomain transcription factors. It plays a critical role in regulation of multiple organ functions by promoting gene expression, such as thyroid hormone in thyroid and surfactant proteins in the lung. However, molecular regulation of TTF1 has not been well investigated, especially regarding its protein degradation. Here we show that protein kinase C agonist, phorbol esters (PMA), reduces TTF1 protein levels in time- and dose-dependent manners, without altering TTF1 mRNA levels. TTF1 is ubiquitinated and degraded in the proteasome in response to PMA, suggesting that PMA induces TTF1 degradation in the ubiquitin-proteasome system. Furthermore, we demonstrate that an E3 ubiquitin ligase, named HECT, C2 and WW domain containing E3 ubiquitin protein ligase 1 (HECW1), targets TTF1 for its ubiquitination and degradation, while downregulation of HECW1 attenuates PMA-induced TTF1 ubiquitination and degradation. A lysine residue lys151 was identified ubiquitin acceptor site within the TTF1. A lys151 to arginine mutant of TTF1 (TTF1K151R) is resistant to PMA- or HECW1-mediated ubiquitination and degradation. Further, we reveal that overexpression of TTF1 increases lung epithelial cell migration and proliferation, while the effects are reversed by HECW1. This study is the first to demonstrate that the E3 ubiquitin ligase HECW1 regulates TTF1 degradation by site-specific ubiquitination. This study will provide a new direction to clarify the molecular regulation of TTF1 in lung and its role in lung epithelial remodeling after injury.